Demography of a stable population of Crab Plovers wintering in Oman - Bom, R; van Gils, J; Oosterbeek, K; Deuzeman, S; de Fouw, J; Kwarteng, A; Kentie, R (Springer Berlin Heidelberg, 2018)
The monotypic Crab Plover Dromas ardeola winters around the shores of the Indian Ocean and breeds in colonies on islands around the Arabian Peninsula. The IUCN lists the world population of Crab Plovers as stable, but long-term survey data or demographic estimates regarding the species status are lacking. Here, we use survey and demographic data collected from 2011 to 2015 to study the status of the population of Crab Plover at their most important wintering area: the Barr Al Hikman Peninsula in the Sultanate of Oman. Our survey data showed that the population of Crab Plovers initially increased and then stabilized. The overall observed finite rate of population change ( $\bar{λ }_{\text{obs}}$) was estimated at 1.004 (0.995–1.013 95% Bayesian credible interval [BCI]), indicating a stable population (7000–9000 birds), that is possibly at carrying capacity. Based on mark-recapture data, the mean annual apparent survival probability of Crab Plovers was estimated to be 0.90 (0.85–0.94 95% BCI). We used counts of adults and yearlings to estimate the mean annual fecundity rate at 0.06 young per pair. Using these demographic values, the overall mean expected finite rate of population change ( $\bar{λ }_{ \exp }$) was estimated to be 0.949 (0.899–0.996 95% BCI), so there is a low chance that $\bar{λ }_{\text{obs}}$ and $\bar{λ }_{ \exp }$ overlap. $\bar{λ }_{\text{obs}}$ and $\bar{λ }_{ \exp }$ would completely match if about 450 Crab Plovers immigrate to Barr Al Hikman each year. Regional surveys show that yearling densities are higher closer to the breeding areas, so immigrants could be birds that during their first winter stayed close to their natal area. Our study support the IUCN listing of Crab Plover as stable, but further population-wide monitoring is required. From a conservation point of view it is important to continue monitoring because Crab Plovers breed and winter in a region that is rapidly developing.